2013
DOI: 10.1002/etc.2385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a chronic lower range of triclosan exposure on a stream mesocosm community

Abstract: Triclosan (5-chloro-2-(2,4-dichlorophenoxy)phenol) is an antimicrobial found in consumer soaps and toothpaste. It is in treated wastewater effluents at low parts-per-billion concentrations, representing a potentially chronic exposure condition for biota inhabiting receiving streams. For the present study, a naturally colonized benthos was created using flow-through indoor mesocosms; then, the benthic communities were dosed to achieve different in-stream triclosan concentrations (control, 0.1 μg/L, 0.5 μg/L, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 58 publications
1
56
0
Order By: Relevance
“…TCS effects on a microbial community may occur both directly (toxicity) and indirectly (ecological interactions), as indicated previously (Nietch et al, 2013;Lawrence et al, 2009). Hypothetically, longer exposures may cause greater indirect effects on the microbial community through effects on bacterial-phototroph interactions and grazing, as seen in this study (see below).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…TCS effects on a microbial community may occur both directly (toxicity) and indirectly (ecological interactions), as indicated previously (Nietch et al, 2013;Lawrence et al, 2009). Hypothetically, longer exposures may cause greater indirect effects on the microbial community through effects on bacterial-phototroph interactions and grazing, as seen in this study (see below).…”
Section: Discussionmentioning
confidence: 84%
“…Cyanobacteria, such as Anabaena flos-aquae, are also sensitive with a NOEC of 0.67 g l −1 . In contrast, Nietch et al (2013) reported that based on enumeration of identified taxa and Chl-a determinations, stimulation occurred at low doses (0.1 g l −1 TCS) relative to the control but suppression at 5 and 10 g l −1 doses over an extended exposure. For example, cyanobacteria were stimulated at <1 g l −1 , although there were mostly undetectable effects at 5 and 10 g l −1 .…”
Section: Response Of Phototrophsmentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, triclosan, another antimicrobial with broad activity against bacteria and many parasitic protists, is a common component of toothpaste, hand-washes, and other manmade products. The ubiquitous presence of triclosan in the environment, as well as long-term human exposure, could contribute to the development of triclosan-resistant pathogens (18) or microbial resistance to other drugs that share similar modes of action, such as the antituberculosis drug, isoniazid (19). Although a link between environmental triclosan levels and antibiotic resistance has yet to be established (20), the study by Perry et al (2) provides a cautionary lesson.…”
mentioning
confidence: 99%